DNase improves the efficacy of antimicrobial photodynamic therapy in the treatment of candidiasis induced with Candida albicans - Jordão, Cláudia Carolina; Klein, Marlise Inêz; Barbugli, Paula Aboud; Mima, Ewerton Garcia de Oliveira; de Sousa, Tábata Viana; Ferrisse, Túlio Morandin; Pavarina, Ana Claudia (Frontiers in Microbiology, 2023)
The study evaluated the association of DNase I enzyme with antimicrobial photodynamic therapy (aPDT) in the treatment of oral candidiasis in mice infected with fluconazole-susceptible (CaS) andresistant (CaR) Candida albicans strains. Mice were inoculated with C. albicans, and after the infection had been established, the tongues were exposed to DNase for 5 min, followed by photosensitizer [Photodithazine®(PDZ)] and light (LED), either singly or combined. The treatments were performed for 5 consecutive days. Treatment efficacy was evaluated by assessing the tongues via fungal viable population, clinical evaluation, histopathological and fluorescence microscopy methods immediately after finishing treatments, and seven days of follow-up. The combination of DNase with PDZ-aPDT reduced the fungal viability in mice tongues immediately after the treatments by around 4.26 and 2.89 log10 for CaS and CaR, respectively (versus animals only inoculated). In the fluorescence microscopy, the polysaccharides produced by C. albicans and fungal cells were less labeled in animals treated with the combination of DNase with PDZ-aPDT, similar to the healthy animals. After 7 days of the treatment, DNase associated with PDZ-aPDT maintained a lower count, but not as pronounced as immediately after the intervention. For both strains, mice treated with the combination of DNase with PDZ-aPDT showed remission of oral lesions and mild inflammatory infiltrate in both periods assessed, while animals treated only with PDZ-aPDT presented partial remission of oral lesions. DNase I enzyme improved the efficacy of photodynamic treatment.